Incidence of vertebral fracture in europe: results from the European Prospective Osteoporosis Study (EPOS). - Felsenberg, D; Silman, A; Lunt, M; Armbrecht, G; Ismail, A; Finn, J; Cockerill, W; Banzer, D; Benevolenskaya, L; Bhalla, A; Bruges Armas, J; Cannata, J; et al. (2002)
Vertebral fracture is one of the major adverse clinical consequences of osteoporosis; however, there are few data concerning the incidence of vertebral fracture in population samples of men and women. The aim of this study was to determine the incidence of vertebral fracture in European men and women. A total of 14,011 men and women aged 50 years and over were recruited from population-based registers in 29 European centers and had an interviewer-administered questionnaire and lateral spinal radiographs performed. The response rate for participation in the study was approximately 50%. Repeat spinal radiographs were performed a mean of 3.8 years following the baseline film. All films were evaluated morphometrically. The definition of a morphometric fracture was a vertebra in which there was evidence of a 20% (+4 mm) or more reduction in anterior, middle, or posterior vertebral height between films--plus the additional requirement that a vertebra satisfy criteria for a prevalent deformity (using the McCloskey-Kanis method) in the follow-up film. There were 3174 men, mean age 63.1 years, and 3,614 women, mean age 62.2 years, with paired duplicate spinal radiographs (48% of those originally recruited to the baseline survey). The age standardized incidence of morphometric fracture was 10.7/1,000 person years (pyr) in women and 5.7/1,000 pyr in men. The age-standardized incidence of vertebral fracture as assessed qualitatively by the radiologist was broadly similar-12.1/1,000 pyr and 6.8/1,000 pyr, respectively. The incidence increased markedly with age in both men and women. There was some evidence of geographic variation in fracture occurrence; rates were higher in Sweden than elsewhere in Europe. This is the first large population-based study to ascertain the incidence of vertebral fracture in men and women over 50 years of age across Europe. The data confirm the frequent occurrence of the disorder in men as well as in women and the rise in incidence with age.